A condição docente: um estudo das condições de trabalho dos professores do Centro de Estudos Sociais Aplicados da Universidade Estadual do Ceará - Pereira, Alessandra da Silva (2013)
The research concentrates the analysis on the faculty member work at “Universidade Estadual do Ceará” having as the basis the work conditions of the professors from the social study center and its applicabilites. The specif goals targeted the analyzis and understandin of the changes in the work of the faculty member considering the reformation of the State and the brasilian university and also to understand the state public policy and the teaching in the higler education system in Ceará and the analysis through the profesors perception of CESA about the work conditions at UECE. All the methodologic process was acyvired through bibliographe research, the documental research and the empiric search with the application of quizzes involuing faculty members from CESA. We verified that the transformations in the labor world has a strong impact on the hioher education system and consequently in the work of faculty members mahing it very weal. This has a oirect relation wizh the global capitalism crisis with the extauctural changes of brasilian hiohez educational system an with the estrategles applied by the neo-liberals governments following the instructions of the international institutions, the brasilian government has been delegating to the private sector the responsibilities of financing and applying the higlen education through different private estrategles in the public sector, expanding the rench of money to use. The education policy forms from the neo-liberals proposals intensifies the privatizations, the outsourcing work, the informal work, leanding the faculty work to be very weak. The faculty work area in the highen education has re-estructed in a substantial way. The flexibility of the hiring process has imposed itself in the private and publics IES. The hiring process of professors for substitution work has been increased and this forces a strong intensification of work hours not only in the environment but also affects the family and personal life furthermore there are no adequate working conditions, if we consider that, most of time the equipment and also the ergonomic conditions are inefficient and non-existent.